Strategy For Implementing A Compassionate Approach In Islamic Education According To The View Of The Qur'an - Ainal Mardhiah; Musradinur; Syafruddin; Khima Milidar; Evi Yuliana (International journal of technology and education research, 2026)
Violence in education in Indonesia has reach alarming and categorized levels as emergency national, including violence sexual, physical, bullying, to policy discriminatory involving power educator and participant educate as the perpetrator. Research This aim analyzing implementation strategies approach love love (mercy) in Islamic education according to perspective of the Qur'an. Type research used is study qualitative with approach studies library research, where primary data is sourced from the Qur'an and hadith, while secondary data sourced from journal scientific, books, and research relevant previous research results. disclose four main strategies implementation approach love Dear. First, role model and empathy educator with become figure compassionate who reflects the nature of Rauf and Rahim and active listen participant educate. Second, communication soft and comprehensive with avoid punishment physical, using approach dialogical, as well as give appreciation and praise. Third, learning inclusive and humanistic with recognize uniqueness every participant educate and implement draft love of Allah and the Messenger. Fourth, grow love Darling between fellow through learning collaborative and action social research This conclude that approach love Darling is the fundamental foundation of Islamic education which is rooted in QS. Ali Imran verse 159, where gentleness more effective than violence in guide human. Implementation results study This recommend implementation approach love Darling in a way consistent in the environment family, school, and community For form generation faithful, moral noble, and empathize tall.